Characterization of Ground Water Quality in Southern and Northern Region of Zanzibar Island - Abdul AJM; Lim H; Miza AK (Journal of New Developments in Chemistry, 2021)
Millions of people from different countries depend on groundwater, which might contain elevated levels of unhygienic constituents. Poor quality of drinking water in many countries has been forcing people to use bottled water. In the present study, groundwater samples were collected in November 2014 leading to twenty-nine analysis of groundwater samples. The primary objective of this paper is to study the selected groundwater quality parameters as an establishment of preliminary baselines on groundwater constituents. A total of twenty nine water samples were collected (fourteen and fifteen samples from North and South regions of Zanzibar Island respectively. Physical parameters (Turbidity, oxidation-reduction potential ORP, Eh, pH, total dissolved soild TDS, salinity, and Electrical conductivity (EC) were determined in situ using Horiba multiparameters digital meters. Analysis of anions (NO3-, Br- , SO42-, F-, NO2-) was carried out using Ion chromatography (IC). Nitrite and nitrate for some water were below detection limit (BDL) The order of relative abundance for anions in samples collected at Northern region of Zanzibar Island, was NO3- > Br- > SO42- > F- > NO2- , while for the Southern region the order was NO3- >Br- > NO2- > SO42- > F- . In both regions, the orders for other parameters were; Turbidity > pH > salinity; and EC >TDS > ORP > Eh. Almost all the measured parameters were within the WHO guidelines for drinking water. However, for nitrate and bromide, the percentage that exceeded the WHO limit was 7%, and 10.3% respectively. Based on toxicological perspective, although few samples had concentrations above groundwater quality criterion it is fundamental to estimate the intake by humans through the drinking water pathways.
Keywords: Drinking water